Determination of copolymerization constants of sodium methacrylate and sodium 2-acrylamido-2-methylpropanesulfonate - Yakimtsova, Liudmila B.; Kievitskaya, Darya V. (Journal of the Belarusian State University. Chemistry, 2018)
Copolymers of sodium methacrylate and sodium 2-acrylamido-2-methylpropanesulfonate with different content of monomeric units were synthesized by radical polymerization in aqueous solution for the first time. The composition of the copolymers was evaluated by infrared spectroscopy. The Finemann – Ross and Kelen – Tüdos methods have been used to determine the copolymerization constants, the statistical distribution of units and reduction of the copolymer with sodium methacrylate units were established.
Keywords: radical copolymerization; sodium methacrylate; sodium 2-acrylamido-2-methylpropanesulfonate; co polymerization constants; Finemann – Ross and Kelen – Tüdos methods